Analisis Pengaruh Perubahan Penggunaan Lahan terhadap Debit Sungai (Studi Kasus : Sub DAS Cikeas): Analysis of Land Use Change Influence to River Discharge (Study Case: Cikeas Sub-Basin ) - I Gede Aditya Dharma; Roh Santoso Budi Waspodo; Nora Pandjaitan (Departemen Teknik Sipil dan Lingkungan, IPB University, 2021)
Land use change have an impact on infiltration capacity. There is often an annual flood on Kadumanggu District. When the rainfall is high so the river will be overflow. The outlet of Cikeas sub-basin was located on Kadumanggu District. This research aimed to determine the maximum discharge of the Cikeas River and analyze the relation between land use change and discharge of Cikeas River. The research was conducted by delineating the water catchment area, analyzing rainfall, making a land use map and modeling with HEC-HMS. Based on the modeling results, the maximum discharge of the Cikeas River in 2000 was 74.3 m3/s, in 2009 was 84.9 m3/s, and in 2018 was 91.7 m3/s. The catchment area with an extensive use as residential had a higher river discharge compared to the area with a large green area. It meaned that, land use changes greatly affected the river discharge.